The challenges of digital divide and the use of web 2.0 platforms as knowledge sharing tools among Nigerian academics - Gamji, Musa Bara'u; Kara, Nurten; Nasidi, Qaribu Yahaya; Abdul, Aisha Ibrahim (Sage Publications Ltd, 2022)
This paper investigates the challenges affecting knowledge sharing among lecturers using web 2.0 platforms to meet the requirements of the digital age of the 21st century. Knowledge sharing is an exchange of skills, ideas, experience, and understanding among people. The study is base on the digital divide theory, which focuses on discrepancies or inequality of access to the Internet and technological devices. The survey method is adopted, involving 1,287 respondents sampled conveniently from the 13 faculties of the Ahmadu Bello University Zaria, Nigeria. Data was successfully retrieved from 1047 respondents, representing 81.9% and was presented and analyzed through descriptive statistics. The findings revealed that the most significant challenges facing users of web 2.0 platforms are the high cost of data, and an unstable power supply. The result indicates that the most used social media by the academic lecturers of Ahmadu Bello University is WhatsApp, while the most used educational resource site is ResearchGate. The study recommends that the challenge of the high cost of data should be solved by providing uninterrupted broadband and free Internet facilities. The qualitative method should be used to further this study to have users of these platforms from more than one institution.
Keywords: digital divide; knowledge sharing; web 2; 0 applications; academia; social networking sites